2015
DOI: 10.1007/s10562-015-1508-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Water on the Supported Ziegler–Natta Catalysts: Optimization of the Operating Conditions by Response Surface Methodology

Abstract: In this study different water containing adducts, with MgCl 2 ÁnEtOHÁmH 2 O formula, were synthesized through melt quenching method. After characterization of support samples, the final catalysts were prepared by reaction of the samples with TiCl 4 and tested in slurry phase propylene polymerization. The prepared catalysts showed similar stereospecificities but different activities in polymerization experiments, so that, with increasing water amount from m = 0.0 to m = 0.4 wt%, the catalyst activity reached it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…Zirconocene (Cp 2 ZrCl 2 ) and hafnocene (Cp 2 HfCl 2 ) catalysts were commercially obtained from Aldrich Company (Munich, Germany). An MgCl 2 /TiCl 4 ‐based catalyst that was synthesized according to our previous work was used as the ZN catalyst precursor . It contained 3% Ti as the active center.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zirconocene (Cp 2 ZrCl 2 ) and hafnocene (Cp 2 HfCl 2 ) catalysts were commercially obtained from Aldrich Company (Munich, Germany). An MgCl 2 /TiCl 4 ‐based catalyst that was synthesized according to our previous work was used as the ZN catalyst precursor . It contained 3% Ti as the active center.…”
Section: Methodsmentioning
confidence: 99%
“…An MgCl 2 /TiCl 4 -based catalyst that was synthesized according to our previous work was used as the ZN catalyst precursor. 17 It contained 3% Ti as the active center. Ethylene and nitrogen were purchased from Bandar Imam Petrochemical Company (Mahshahr, Iran) and Roham Company (Tehran, Iran), respectively, and were purified by flowing through molecular sieves (3 and 4 Å) and CuO/Al 2 O 3 packed beds to remove oxygen and water residues.…”
Section: Experimental Materialsmentioning
confidence: 99%
“…Because the use of MgC1 2 as a support drastically enhanced the catalyst activity, a great deal of attention has been focused on the development of various effective supports, such as inorganic compounds. [4,5] Nowadays, as two kinds of major industrial materials of the carrier, MgCl 2 ·nROH and magnesium ethoxide, Mg(OEt) 2 , are widely known. [6,7] Although, Mg(OEt) 2 has a morphological subject regarding roundness and particle size distribution as compared with MgCl 2 ·nROH, the catalyst made by Mg(OEt) 2 shows a higher activity.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18] Lately, investigations have shown that doping a suitable amount of Lewis acids in MgCl 2 or Mg(OEt) 2 supports would be an effective way to improve their catalytic performance in α-olefin polymerization. The mostly used doping agents were based on different metal halides such as MnCl 2 , [2] ZnCl 2 , [3] NaCl, [4] AlCl 3 [5,6,19], and the mixture of metal halide with metalloids like ZnCl 2 -SiCl 4 system. [7,8] These agents not only can have notable effect on catalyst activity but also have the ability to change catalyst efficiency toward higher α-olefins in LLDPE production as well as stereo-regularity of final polymer in propylene polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…The Ziegler-Natta catalyst was prepared according to our previous paper. [13] It was based on MgCl 2 /ethanol adduct, in which 3.3% Ti was loaded in TiCl 4 form. Triethylaluminium (TEAL, 2.7 M, as cocatalyst) and cyclohexyl methyl dimethoxy silane (CMMS, as external donor) were purchased from Sigma-Aldrich and used as received.…”
Section: Methodsmentioning
confidence: 99%